Food Security Innovation: Research by Robert Bertram, USAID - Bertram, Robert (2014)
IFPRI-IRRI Policy Seminar “Innovations in Science and Policy: Transforming the Rural Sector for Improved Food Security” on September 26, 2014. Presentation by Robert Bertram, Chief Scientist, Bureau for Food Security, USAID.